2016
DOI: 10.12775/cjfa.2016.010
|View full text |Cite
|
Sign up to set email alerts
|

Accountancy-Based Sources of Information for Planning Purposes in SMEs

Abstract: Abstract:The present paper's research objective is to reveal the specifics and capabilities of the accountancy to serve as an information base for planning of the business of SMEs. In this regard, a research method (a survey) focusing on study of documentation in a number of Bulgarian SMEs has been carried out. Based on the results gained after the implementation of the research method, main sources of information for planning purposes in SMEs have been synthesized and evaluated. The main conclusions are that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The aim is to study the opinion of the business community in the knitwear industry related to potential adaptations of the strategic management accounting tools and their easier application by SMEs. Similar successful attempts have already been made and described in previous publications (Papazov & Mihaylova, 2009;Papazov & Mihaylova, 2015;Papazov & Mihaylova, 2016). Of course, the fact that the specifics of the industry affect the accountability of SMEs is also considered.…”
Section: Specifics Of the Accounting In Smes Sample And Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…The aim is to study the opinion of the business community in the knitwear industry related to potential adaptations of the strategic management accounting tools and their easier application by SMEs. Similar successful attempts have already been made and described in previous publications (Papazov & Mihaylova, 2009;Papazov & Mihaylova, 2015;Papazov & Mihaylova, 2016). Of course, the fact that the specifics of the industry affect the accountability of SMEs is also considered.…”
Section: Specifics Of the Accounting In Smes Sample And Methodssupporting
confidence: 58%
“…Previous research has shown that external accountants in Bulgaria are reluctant to provide SMEs' owners or managers with sufficient management accounting information for decision-making (Papazov & Mihaylova, 2016). Lack of strategic accounting information is one of the main difficulties for strategic management.…”
Section: Analysis Of the Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation